2017
DOI: 10.4236/ojf.2017.72014
|View full text |Cite
|
Sign up to set email alerts
|

Adapted REDD plus Based on Local People’s Capabilities: A Case Study from Luang Prabang Province, Lao PDR

Abstract: The reducing emissions from deforestation and forest degradation (REDD plus) has been proposed as a key tool for reducing greenhouse gases (GHG) from deforestation and forest degradation in land use sector. The development of a REDD plus that considers national, sub-national, and/or local circumstances in relation to a target area requires an analysis of site-specific deforestation drivers and land use characteristics. This study aimed to analyze the capability of forest-dependent people to find the way for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Additionally, comments from focal group discussions with village authorities indicated that the Hmong were good at maintaining their livelihood by planning ahead. They also tended to have more family members than the Khmu, which provided a larger labor force [23,34]. Therefore, the Hmong can be viewed as well-positioned to benefit from new land-use activities.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, comments from focal group discussions with village authorities indicated that the Hmong were good at maintaining their livelihood by planning ahead. They also tended to have more family members than the Khmu, which provided a larger labor force [23,34]. Therefore, the Hmong can be viewed as well-positioned to benefit from new land-use activities.…”
Section: Discussionmentioning
confidence: 99%